Leadership Strategies to Boost Loyalty and Career Development for Alfamart Kedaton Lampung Selatan Employees - Nurmansyah, Nurmansyah; Rozi, Fakhrur (Journal of Business Administration and Strategy, 2025)
This study aimed to analyze the leadership strategies implemented at the Alfamart Kedaton Lamsel store in improving employee loyalty and career development. Effective leadership plays an important role in creating a conducive work environment and encouraging employee growth. The research method used is descriptive qualitative with data collection techniques through interviews. The results of this study indicate that transformational and participatory leadership have a positive influence on employee loyalty, as evidenced by high retention rates and increased job satisfaction. Additionally, career development is facilitated through performance evaluations and the provision of promotion opportunities. This study recommends the importance of ongoing leadership training for managers to ensure that the strategies employed remain relevant and effective in supporting human resources.